Metode Drill dalam Penguasaan Kosakata Bahasa Jerman - Reski Sri Wulandari; Syarifah Fatimah Al Ilmul (Phonologie : Journal of Language and Literature, 2023)
Abstract. The purpose of this study was to determine the increase in German vocabulary mastery of class XI students at SMA Negeri 14 Gowa through the application of the Drill method. This type of research is classroom action research which consists of two cycles with each cycle consisting of two meetings. The subject of this study was class XI Mipa 3 SMA Negeri 14 Gowa. There are two types of this research, namely qualitative data and quantitative data. Qualitative data were obtained from teacher and student observation data, while quantitative data were obtained from students' German vocabulary tests. The results of students' German vocabulary tests in cycle I obtained an average of 69.5 and experienced an increase in cycle II with an average value of 84.7. The results of this test show that the application of the Drill method can increase the German vocabulary of class XI students of SMA Negeri 14 Gowa.Keyword: Implementation, Vocabulary, Drill Method